Physical Exercise System Structure with Tools for Preschool Children 4-5 Years old Hanoi City - Yen, Nguyen Thi (International Journal of Humanities and Education Development (IJHED), 2023)
Structure of physical exercise system with equipment for preschool children 4-5 years old Hanoi City: The structure of the physical exercise system with equipment for 4-year-old preschool children in Hanoi City, of 8 groups with 35 exercises with equipment for the age of 4 is (1) Group of movement exercises; (2) Group of stretching exercises; (3) Group of exercises that stimulate height growth; (4) Group of orientation exercises; (5) Group of exercises for upper limb development; (6) Group of exercises for lower limb development; (7) Group of skillful development exercises; (8) Group of mixed exercises. Structure of physical exercise system with equipment for 5-year-old preschool children in Hanoi City, including 35 exercises of 8 groups oriented to physical development of 5-year-old children: (1) Group of movement exercises; (2) Group of stretching exercises; (3) Group of exercises that stimulate height growth; (4) Group of orientation exercises; (5) Group of exercises for upper limb development; (6) Group of exercises for lower limb development; (7) Group of skillful development exercises; (8) Group of mixed exercises.